Static, Dynamic, And Notch Toughness - Discussion (c612d3d9-51d3-42d9-bc41-b1857ea54bbe) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1919)
JOHN H . NELSON,*Worcester, Mass.-In reply to the question "Is there any final information in regard to the relation between the temperature or the rate of cooling of a piece of heat-treated steel from the drawing temperature, and the so-called notch toughness?" I might say that we have conducted a large series of tests in the study of impacts on chrome-nickel and carbon steels and have gone into the subject of quenching from drawing temperature quite thoroughly but have found that one cannot lay down any definite rule or law with respect to the effect of quenching from the drawing heat. We conducted experiments on the effect of cooling by quenching in water, cooling in air, and burying the coupon in lime. Steels that have practically no impact value when air cooled may show very marked results when they are quenched in water, depending on the temperature at which the drawing is done.